2020
DOI: 10.20524/aog.2020.0449
|View full text |Cite
|
Sign up to set email alerts
|

Direct-acting antiviral treatment for chronic hepatitis C in people who use drugs in a real-world setting

Abstract: Background Direct-acting antivirals (DAAs) offer high cure rates in people who inject drugs (PWID) with hepatitis C virus (HCV) infection. There are concerns regarding lower response rates among PWID in real life. We evaluated the outcome of DAA therapy in PWID in a real-world setting and the factors that affect it. Methods We performed a retrospective analysis of 174 PWID with chronic hepatitis C who started DAAs in a Greek liver clinic in collaboration with an addiction program. Patients who did not return f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
(47 reference statements)
1
10
2
Order By: Relevance
“…Notably, a high number of LTFU patients had co‐morbidities of drug abuse, drug substitution therapy and psychiatric disorders. In other real‐world DAA studies, similar SVR12 differences in PP and ITT populations were observed in patients who use drugs and patients on opioid substitution therapy, due to a high number of patients LTFU 13‐16 . Whilst clinical trial data demonstrated high SVR12 rates in these vulnerable patients, failure to report for SVR results continues to remain a barrier for HCV care in real‐world settings 13‐15,17,18 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Notably, a high number of LTFU patients had co‐morbidities of drug abuse, drug substitution therapy and psychiatric disorders. In other real‐world DAA studies, similar SVR12 differences in PP and ITT populations were observed in patients who use drugs and patients on opioid substitution therapy, due to a high number of patients LTFU 13‐16 . Whilst clinical trial data demonstrated high SVR12 rates in these vulnerable patients, failure to report for SVR results continues to remain a barrier for HCV care in real‐world settings 13‐15,17,18 .…”
Section: Discussionmentioning
confidence: 73%
“…In other real‐world DAA studies, similar SVR12 differences in PP and ITT populations were observed in patients who use drugs and patients on opioid substitution therapy, due to a high number of patients LTFU 13‐16 . Whilst clinical trial data demonstrated high SVR12 rates in these vulnerable patients, failure to report for SVR results continues to remain a barrier for HCV care in real‐world settings 13‐15,17,18 . Whilst this does not indicate withholding treatment from these patient populations, they may require additional support measures to prevent LTFU, achieve SVR, and reach World Health Organization (WHO) elimination targets.…”
Section: Discussionmentioning
confidence: 88%
“…DAAs as treatment options against all of the HCV genotypes have been crucial in curtailing the spread of the virus. Their use has led to a greater than 90% cure rate even among PWUD [ 50 , 51 ]. Therefore, a focus on treating PWUD communities with DAAs could be highly effective in controlling the transmission of HCV among this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…While there has been evidence for lower response rates to DAA treatment in HCV populations with parallel injectable recreational drug use, a 2020 study led by Koustenis et al [ 42 ] offers real-world data that sustained virological response to DAAs is possible in high-risk patients who inject drugs[ 42 ]. This is in keeping with established trends revealing similar treatment responses in these higher-risk populations to that of the general population[ 42 ]. However, adherence and loss to follow-up remain ongoing concerns among high-risk populations, and during the study, over 10% of patients who inject drugs were lost to follow-up during or after treatment[ 42 ].…”
Section: Out With the Old In With New–novel Therapeutics In The Treatment Of Hcvmentioning
confidence: 99%
“…However, adherence and loss to follow-up remain ongoing concerns among high-risk populations, and during the study, over 10% of patients who inject drugs were lost to follow-up during or after treatment[ 42 ]. The risk of being lost to follow-up was correlated with several factors, including younger age and parallel recreational drug use[ 42 ].…”
Section: Out With the Old In With New–novel Therapeutics In The Treatment Of Hcvmentioning
confidence: 99%